PEMANFAATAN LINGKUNGAN SEKITAR SEBAGAI SUMBER BELAJAR IPA PADA SISWA SD KELAS TINGGI - Niza Nurul Husna; Haifaturrahmah; Yuni Mariyati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to systematically examine the use of the surrounding environment as a learning resource for Science Education among upper-grade elementary school students. Employing a Systematic Literature Review (SLR) approach, this research analyzed various scientific publications released between 2015 and 2025 that explored the implementation of environmental-based learning. The analysis revealed that integrating the surrounding environment into science learning significantly enhances students’ learning outcomes, motivation, engagement, and conceptual understanding. The environment serves as a natural laboratory, providing concrete and contextual learning experiences aligned with students’ concrete operational development stage. Several teaching strategies, including Project-Based Learning (PjBL), Contextual Teaching and Learning (CTL), and Outdoor Study, were found effective in bridging theory and practice while fostering environmental awareness. However, some challenges persist, such as limited time, inadequate facilities, and teachers’ insufficient ability to design environmental-based learning. Beyond academic advantages, this approach contributes to character building and supports the strengthening of the Pancasila Student Profile. Therefore, this study recommends continuous teacher training and supportive school policies to optimize the implementation of environmental-based science learning in elementary schools.